A novel function for CRISP1 in rodent fertilization: involvement in sperm-zona pellucida interaction - Busso, Dolores (2007)
Epididymal protein CRISP1 participates in rat and mouse gamete fusion through its interaction with complementary sites on the egg surface. Based on in vivo observations, in the present study we investigated the possibility that CRISP1 plays an additional role in the sperm-zona pellucida (ZP) interaction that precedes gamete fusion. In vitro fertilization experiments using zona-intact rat and mouse eggs indicated that the presence of either an antibody against rat CRISP1 (anti-CRISP1) or rat native CRISP1 (rCRISP1) during gamete co-incubation produced a significant decrease in the percentage of fertilized eggs. However, differently to that expected for a protein involved in gamete fusion, no accumulation of perivitelline sperm was observed, suggesting that the inhibitions occurred at the sperm-ZP interaction level. Bacterially expressed recombinant CRISP1 (recCRISP1) also significantly inhibited egg fertilization. In this case, however, an increase in the number of perivitelline sperm was observed. Subsequent experiments evaluating the effect of anti-CRISP1 or rCRISP1 on the number of sperm bound per egg indicated that the protein is involved in the initial step of sperm-ZP binding. In agreement with these functional studies, indirect immunofluorescence experiments revealed that although rCRISP1 is capable of binding to both the ZP and the oolema, recCRISP1 only binds to the egg surface. The finding that deglycosylated rCRISP1 behaves as the untreated protein, whereas the heat-denatured rCRISP1 associated only with the oolema, indicates that the protein ZP-binding ability resides in the conformation rather than in the glycosydic portion of the molecule. The interaction between rCRISP1 and the ZP reproduces the sperm-ZP-binding behavior, as judged by the failure of the protein to interact with the ZP of fertilized eggs. Together, these results support the idea that CRISP1 participates not only in sperm-egg fusion but also in the prior stage of sperm-ZP interaction.